Five varsities make top 200 in Asia Pacific education list - Malay, Mail (Malay Mail, 2017)
KUALA LUMPUR ― Five Malaysian universities made the top 200 of this year’s Times Higher Education (THE) best Asia Pacific schools list, led by Universiti Putra Malaysia and Universiti Teknologi Malaysia in the joint 121-130 band.